Spatial Relationship Perception is Not Affected by Short-term Cortical Reorganization - Carlo Aleci; Claudio Rosa; Alessia Mazzon (Archives of Current Research International, 2022)
Aims: Long-term cortical reorganization after cortical damage can induce abnormal spatial relationship perception (spatial anisotropy) but there is also evidence of short-term, reversible cortical re-modulation even in the absence of cerebral damage: simulated hemianopic deprivation, in fact, is found to affect the positional judgment. This study investigates if the same occurs for spatial relationship perception. Study Design: Case series. Place and duration of Study: Service of Neuro-Ophthalmology, University of Turin, Italy, from January 2020 to July 2020. Methodology: Spatial relationship perception (SRP) of three subjects was measured in the presence of simulated homonymous hemianopia with a psychophysical procedure that estimates the discrimination threshold between elliptical and circular stimuli centered to the fixation point. The extent of the deprivation was graded as the distance of the proximal border of the nonresponsive area from the fixation point. Results: Overall, spatial relationship perception is not affected by the hemifield deprivation in terms of distance of the scotoma from the fixation point (P= 0.26), laterality (P= 0.07), and distance X laterality (P= 0.15). However, a significant effect of distance and laterality (P= 0.01 and P= 0.02, respectively) was found in the sole observer who showed an anisotropic perception in normal (no-simulated) condition. Conclusion: SRP appears to be robust toward the reversible spatial remapping induced by simulated hemianopia along the deprived area. However, the response of the visual system to artificial visual deprivation seems conditioned by pre-existing anisotropy.